Lesson Study: uma experiência com três professores de inglês da rede pública estadual em Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
The present study presents the results of the application of a Lesson Study cycle in a state public school in the city of Santarém-PA. The purpose of this study was to identify contributions to the professional development that three English teachers participating in the research attribute to the use of the Lesson Study. As specific objectives, the study aimed to: (a) identify the professional development actions and activities that the teachers involved in the research have access to or usually participate in; (b) identify the impressions produced by the participating teachers in relation to the Lesson Study practice; (c) describe how the participation of teachers occurred during Lesson Study activities; and (d) identify the main difficulties teachers face in their participation in Lesson Study activities. This qualitative research is characterized as a case study (YIN, 1984), in the participant observation modality (MAY, 2004; QUEIROZ et al., 2007), and observed the following methodological procedures: bibliographic review and field research with the following steps: (i) formative meetings on Lesson Study and (ii) implementation of a Lesson Study cycle with two iterations of a research lesson. For the collection of data we use the following methods: 1) record of observations made by the researcher; 2) audio and video recording of all phases of application of the Lesson Study; 3) semi-structured interviews before and after the application of the Lesson Study cycle; 4) Lesson Study reflection logs (STEPANEK et al., 2007); and 5) chat log via Whatsapp. The data were analyzed through thematic analysis (GUEST; MACQUENN; NAMEY, 2011). Our discussion has as theoretical support authors such as Nóvoa (1999; 2009), Shulman (1986), Lewis (2012) Cerbin and Kopp (2011), Stepanek et al. (2007), Lave and Wenger (1991). On the one hand, the results show that the teachers considered the teamwork provided by the Lesson Study as a factor of extreme relevance, allowing them to reflect on the quality of their teaching practice for effective student learning. The results point, on the other hand, some difficulties for the participation of the teachers, as the lack of time due to the excessive workload. In spite of this, the teachers favored the diffusion of the methodology in Brazil, concomitant with transformative actions in the educational system.
Keywords: Desenvolvimento profissional; Lesson Study; Pesquisa de aula; estudos de aula; Escola Pública; Educação Básica; Amazônia; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS; EDUCAÇÃO